Some results on the beta function and the incomplete beta function - Mongkolsery Lin (2018)
© 2015 World Scientific Publishing Company. The incomplete Beta function B(a,b; x) is defined for a,b > 0 and 0 < x < 1. This definition was extended to negative integer values of a and b by Özç et al. using neutrix limits. Partial derivatives of the incomplete Beta function B(a,b; x) for negative integer values of a and b were then evaluated. In the following, a number of results are obtained for the incomplete Beta function B(a,b; x) and then the corresponding results for the Beta function B(a,b) are deduced.